Pimple-head and curly - Bone, Ian; Smith, Craig (Walker London, 2002)
The River Gang girls have got it in for Rosie. They used to be her friends, but now they call her Pimple-head. They make fun of her dog, too. Worst of all they've turned the new girl, Curly, against her. Is she brave enough to risk being laughed at and make a stand? Suggested level: primary, intermediate